Calcifying aponeurotic fibroma of the sole of the foot in an elderly patient. (September 2019) - Garcia Navas, Francisco Manuel; Fernandez, Nuria; Lopez, Alberto; Montero, Pedro
Highlights: The present case reports the imaging findings of calcifying aponeurotic fibroma with pathologic correlation in an elderly patient. Although rare, calcifying aponeurotic fibroma should be considered in the differential diagnosis of elderly patients with a calcified soft tissue mass, in particular in the sole of the foot. Abstract: Calcifying aponeurotic fibroma (CAF) is a rare, locally aggressive fibroblastic lesion that occurs predominantly in the distal extremities of children and adolescents. In the present study, a case of pathologically proven CAF arising in the sole of the right foot of a 84-year-old man is presented. Physical examination revealed a firm, immobile, non-tender mass. Plain radiographs showed a faintly calcified soft tissue mass without bone involvement. Magnetic resonance imaging (MRI) revealed a well circumscribed subcutaneous mass. The patient underwent an excisional biopsy. Histologically, the tumor showed a biphasic pattern, composed of a moderately cellular fibromatosis-like component and irregular calcified areas with polygonal epithelioid cells. There has been no evidence of local recurrence six months following surgery. To the best of our knowledge, this case describes the oldest patient with this condition.